Biomechanical Cadaveric Evaluation of Partial Acute Peroneal Tendon Tears. (June 2018) - Wagner, Emilio; Wagner, Pablo; Ortiz, Cristian; Radkievich, Ruben; Palma, Felipe; Guzmán-Venegas, Rodrigo
Background: No clear guideline or solid evidence exists for peroneal tendon tears to determine when to repair, resect, or perform a tenodesis on the damaged tendon. The objective of this study was to analyze the mechanical behavior of cadaveric peroneal tendons artificially damaged and tested in a cyclic and failure mode. The hypothesis was that no failure would be observed in the cyclic phase. Methods: Eight cadaveric long leg specimens were tested on a specially designed frame. A longitudinal full thickness tendon defect was created, 3 cm in length, behind the tip of the fibula, compromising 66% of the visible width of the peroneal tendons. Cyclic testing was initially performed between 50 and 200 N, followed by a load-to-failure test. Tendon elongation and load to rupture were measured. Results: No tendon failed or lengthened during cyclic testing. The mean load to failure for peroneus brevis was 416 N (95% confidence interval, 351–481 N) and for the peroneus longus was 723 N (95% confidence interval, 578–868 N). All failures were at the level of the defect created. Conclusion: In a cadaveric model of peroneal tendon tears, 33% of remaining peroneal tendon could resist high tensile forces, above the physiologic threshold. Clinical Relevance: Some peroneal tendon tears can be treated conservatively without risking spontaneous ruptures. When surgically treating a symptomatic peroneal tendon tear, increased efforts may be undertaken to repair tears previously considered irreparable.